Asymmetric synthesis approach of enantiomerically pure spiro-indenoquinoxaline pyrrolidines and spiro-indenoquinoxaline pyrrolizidines. Issue 20 (1st November 2015) - Shahrestani, Naeimeh; Salahi, Farbod; Tavakoli, Niloofar; Jadidi, Khosrow; Hamzehloueian, Mahshid; Notash, Behrouz
Graphical abstract